An Evaluation of the Lesson Plan Manual for Language Arts in Junior Secondary Schools in Southern Sierra Leone - Libbie, Josephus K. L.; Challay, Saidu; Mbavai, Joseph J.; Senesie, Samuel M. B. (International Journal of Language and Literary Studies, 2026)
Questions continue to be raised about the effectiveness of the Lesson Plan Manual (LPM) because pupils’ performance in Language Arts remained low. Thus, it became necessary to evaluate the LPM to determine whether it is aligned with lesson planning best practices around the world. The research questions raised in the study are: Are the language contents of the LPM clear in terms of examples given, guided and independent practice activities? Does the LPM respond to diversity issues in the Language Arts classroom? Does the LPM have in-built classroom management strategies? Is the LPM flexible enough to deal with changing situations in the classroom? The convergent mixed-method design was used. Out of a population of 458 Language Arts teachers, 210 were used as the sample for quantitative data collection, and Language Arts teachers with at least three years of teaching experience were selected for qualitative data collection. Quantitative data were collected using a self-developed questionnaire. For the collection of qualitative data, a focused group discussion question guide was used. Findings revealed that teachers viewed the LPM as a very useful tool in lesson delivery; the content of the LPM addressed diverse issues in the classroom; the LPM allows teachers to be flexible in adjusting their lessons to the classroom environment and to change their teaching strategies to meet the needs of learners. It is recommended that the Ministry of Basic and Senior Secondary Education conduct symposia for Language Arts teachers to share experiences with the LPM and conduct refresher training regularly on its effective use.